Construction of hierarchically hollow micro-nanostructured surface on polyester via in-situ chlorosilane polymerization and its superhydrophobicity. (26th October 2021) - Xi, Yanni; Liu, Kexin; Wang, Faqiang; Guan, Jinping; Li, Zhanxiong
Abstract: Superhydrophobic fibers based on hierarchically hollow structured surface were prepared for the first time via in-situ growth on polyester, filaments-on-spheres (SF) structures, filaments-and-spheres-on-spheres (FASS) structures and spheres-on-spheres (SS) structures were constructed, exhibiting excellent superhydrophobicity with water contact angles of 158.7 ± 3.4°, 158.5 ± 0.9°, 152.7 ± 3.6° and sliding angles of 1.0 ± 0.7°, 2.3 ± 0.4°, 4.5 ± 0.6°, respectively. More than that, extremely low adhesive force of 74.48 μN was attained. The mechanism of in-situ formation of hollow hierarchical structures on polyester was proposed, and surface chemistry was verified by carrying out X-ray photoelectron spectroscopy and Fourier transform infrared spectroscopy. Moreover, the effect of water absorption on the hydrolysis of chlorosilane was also investigated, showing that wet fabric soaking in solution was of pivotal importance to the hydrolysis condensation polymerization and as-obtained hierarchical structures. Graphical abstract: Image 1 Highlights: Fabrication of superhydrophobic coatings on polyester fabrics via only chlorosilane polymerization. SF structures, FASS structures and SS structures were constructed under different experimental conditions. Possible formation mechanism of hierarchically hollow structures on polyester fabrics was proposed firstly. Superhydrophobic coatings exhibit high contact angle, ultra-low sliding angle and extremely low adhesive force.